A laser pistonphone designed for absolute calibration of infrasound sensors from 10 mHz up to 20 Hz. (1st February 2023) - Rodrigues, D; Vincent, P; Barham, R; Larsonnier, F; Durand, S
Abstract: There has been an increased demand for traceable calibrations at infrasonic frequencies in support of geophysical monitoring applications, an example being the Comprehensive Nuclear-Test-Ban Treaty Organization, which provides global international coverage for a nuclear testing ban, and requires the International Monitoring System. In this paper, a new laser pistonphone design is presented with the objective of establishing primary standards for sound pressure at very low frequencies down to 10 mHz. The piston is a modified accessorized loudspeaker driver whose diameter is equal to the diameter of the front pistonphone cavity. The volume velocity of the piston is measured through a laser interferometer and the current version was designed to have an upper frequency limit of 20 Hz, to overlap with the closed coupler reciprocity method of calibration. Particular attention has been given to the sealing to avoid pressure leakage loss. The dimensions of the front cavity were designed to allow the calibration of a large variety of sensors, including microphones, barometers, manometers and microbarometers. Examples of calibrations for several sensors are presented and also an uncertainty budget for the Brüel & Kjær type 4160 laboratory standard microphones, commonly used for primary calibrations. Finally, the metrological performance of the laser pistonphone is demonstrated by comparing the calibration results with those obtained with alternative methods.